Raskolnikov’s Crime: An Eternal Mystery - Kruszelnicki, Michał (Poznańskie Studia Slawistyczne, 2017)
The article focuses on one of the major mysteries concealed in Fyodor Dostoevsky’s oeuvre up to the present day, namely the main cause of a double murder committed by Raskolnikov in Crime and Punishment. I present selected scholarly interpretations of Raskolnikov’s deed, some of them being already classical and ever inspiring for subsequent readings of the novel, some using extremely persuasive argumentation on one of Raskolnikov’s possible motives. Each of these readings becomes an object of my commentary and critical assessment as I indicate those fragments in Dostoevsky’s novel which undermine their claim to provide an ultimate solution of Raskolnikov’s reason for crime. This presentation leads to the conclusion that Crime and Punishment is unusually open for interpretations, which probably have more to say about the philosophical identity of their authors rather than about Dostoevsky’s intentions in creating his famous protagonists. Eventually I claim that the novel’s main secret – Raskolnikov’s motive for murder – is never to find its one, satisfactory explanation and that this is what makes a literary work a true, immortal masterpiece.